Recycling of composite materials using fluidised bed processes - Fenwick, Neal (1996)
Lightweight engineering plastics have been increasingly used in automotive applications(3), this tends toward more fuel efficient vehicles(1). Glass reinforced plastics commonly include thermosetting polymers. These cannot be re-moulded, unlike thermoplastics, thus thermoset scrap is currently disposed of in landfill. This is increasingly targeted by legislation(14) and is becoming more expensive. This thesis describes work to maximise resource recovery from scrap thermoset composites.